Do Biomarkers of Inflammation, Monocyte Activation, and Altered Coagulation Explain Excess Mortality Between HIV Infected and Uninfected People?. (1st June 2016) - So-Armah, Kaku A.; Tate, Janet P.; Chang, Chung-Chou H.; Butt, Adeel A.; Gerschenson, Mariana; Gibert, Cynthia L.; Leaf, David; Rimland, David; Rodriguez-Barradas, Maria C.; Budoff, Matthew J.; Samet, Jeffrey H.; Kuller, Lewis H.; et al.
Abstract : Background: HIV infection and biomarkers of inflammation [measured by interleukin-6 (IL-6)], monocyte activation [soluble CD14 (sCD14)], and coagulation (D-dimer) are associated with morbidity and mortality. We hypothesized that these immunologic processes mediate (explain) some of the excess risk of mortality among HIV infected (HIV+) versus uninfected people independently of comorbid diseases. Methods: Among 2350 (1521 HIV+) participants from the Veterans Aging Cohort Study Biomarker Cohort (VACS BC), we investigated whether the association between HIV and mortality was altered by adjustment for IL-6, sCD14, and D-dimer, accounting for confounders. Participants were followed from date of blood draw for biomarker assays (baseline) until death or July 25, 2013. Analyses included ordered logistic regression and Cox Proportional Hazards regression. Results: During 6.9 years (median), 414 deaths occurred. The proportional odds of being in a higher quartile of IL-6, sCD14, or D-dimer were 2–3 fold higher for viremic HIV+ versus uninfected people. Mortality rates were higher among HIV+ compared with uninfected people [incidence rate ratio (95% CI): 1.31 (1.06 to 1.62)]. Mortality risk increased with increasing quartiles of IL-6, sCD14, and D-dimer regardless of HIV status. Adjustment for IL-6, sCD14, and D-dimer partially attenuated mortality risk among HIV+ people with unsuppressed viremia (HIV-1 RNA ≥10, 000 copies per milliliter) compared with uninfected people—hazard ratio (95% CI) decreased from 2.18 (1.60 to 2.99) to 2.00 (1.45 to 2.76). Conclusions: HIV infection is associated with elevated IL-6, sCD14, and D-dimer, which are in turn associated with mortality. Baseline measures of these biomarkers partially mediate excess mortality risk among HIV+ versus uninfected people. Abstract : Supplemental Digital Content is Available in the Text.